Studying the Physicochemical Properties of Water Activated by Cold Atmospheric Plasma Jet - Humud, Hammad R.; Hameed, Tamara A. (Iraqi Journal of Science, 2024)
This research aim is to activate water using a plasma jet that works with argon gas and to study the effect of the plasma on the physicochemical properties of the water. The plasma consists of a power supply capable of supplying a high alternating voltage of up to 12 kV in the form of a sinusoidal wave with a frequency of 20 kHz. The temperature of the produced plasma (Te) was (1.028) eV, and its electron density (ne) was (4.392×1017) cm-3 at a flow rate of 1L/min. The physicochemical properties of the water are determined by determining the concentration of each of NO2, NO3, and H2O2, the pH of the water, and the water temperature during exposure to the plasma. The effect of storage time on the properties of the activated water is determined after 48 hours of exposure to plasma. The RONS species were measured using kits purchased from USA (Bartovation) Company manufactured for this purpose. The pH was measured with a pH meter, and the working gas temperature was remotely measured with an IR thermometer. The concentration of the three active species increases with exposure time, but the active species NO2 concentration decreases to zero at an exposure time of 120 minutes. The concentrations of the three components decrease with the decrease in the flow rate. The pH decreases with the exposure time until it reaches 2, and the temperature increases until it reaches 35oC. The concentration of NO3 increases with the increase of the water storage time. In the case of H2O2, the concentration increases slightly, then after 10 hours it begins to decrease exponentially, reaching a value close to zero after the passage of 48 hours. For NO2, its concentration begins to decrease exponentially from the start of storage and reaches a concentration close to zero after 48 hours of storage. The pH increases with the storage time, and the water reaches its natural state with a pH of 7 after 48 hours of storage. From this, it is concluded that the best storage time for PAW is ten minutes after the end of the activation process, and also that the activation time should be short, but not exceeding ten minutes.